\(a)\) Ta có :
\(M=\frac{2\left|x-3\right|}{x^2+2x-15}=\frac{2\left|x-3\right|}{\left(x^2+2x+1\right)-16}=\frac{2\left|x-3\right|}{\left(x+1\right)^2-16}=\frac{2\left|x-3\right|}{\left(x+1\right)^2-4^2}=\frac{2\left|x-3\right|}{\left(x+5\right)\left(x-3\right)}\)
+) Nếu \(x-3\ge0\) \(\Rightarrow\) \(x\ge3\) ta có :
\(M=\frac{2\left|x-3\right|}{\left(x+5\right)\left(x-3\right)}=\frac{2\left(x-3\right)}{\left(x+5\right)\left(x-3\right)}=\frac{2}{x+5}\)
+) Nếu \(x-3< 0\)\(\Rightarrow\)\(x< 3\) ta có :
\(M=\frac{2\left|x-3\right|}{\left(x+5\right)\left(x-3\right)}=\frac{-2\left(x-3\right)}{\left(x+5\right)\left(x-3\right)}=\frac{-2}{x+5}\)
Vậy : +) Nếu \(x\ge3\) thì \(M=\frac{2}{x+5}\)
+) Nếu \(x< 3\) thì \(M=\frac{-2}{x+5}\)
Chúc bạn học tốt ~